2018
DOI: 10.1177/1024907917751301
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and age–gender effects on out-of-hospital cardiac arrest cases

Abstract: Introduction: Temperature is a key factor influencing the occurrence of out-of-hospital cardiac arrest, yet there is no equivalent study in Hong Kong. This study reports results involving a large-scale territory-wide investigation on the impacts of ambient temperature and age-gender differences on out-of-hospital cardiac arrest outcome in Hong Kong. Methods: This study included 25,467 out-of-hospital cardiac arrest cases treated by the Hong Kong Fire Services Department between December 2011 and November 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…All cases were extracted from the Hong Kong emergency call database/dispatch systems and were reported according to the Utstein style 2 , 19 . Incomplete and duplicated records have been excluded and cleaned by the EMS 5 . Each OHCA record was anonymized and contained demographic data (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cases were extracted from the Hong Kong emergency call database/dispatch systems and were reported according to the Utstein style 2 , 19 . Incomplete and duplicated records have been excluded and cleaned by the EMS 5 . Each OHCA record was anonymized and contained demographic data (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors apart from personal characteristics—including environmental, sociodemographic, and geographical influences—can put a person at risk of sudden cardiac arrest. A local study reported that OHCA in Hong Kong showed greater impact on males, the elderly 65+, overweight individuals, and people suffering from cardiovascular and respiratory issues 5 . Also, daily temperature was strongly related to OHCA incidence in Hong Kong, whereby a unit decrease in temperature (°C) would result in a 5.6% increase in OHCA cases 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In the onset population, the effects of cold and heat on OHCA were more pronounced in those with hypertension, diabetes or heart disease [2,5]. At the age of onset, older people are more likely to be affected by these two extreme weather [2,6]. In terms of pathophysiological mechanisms, it is generally believed that the effects of high temperatures and heat waves on OHCA are pathophysiologically due to dehydration [7], Dehydration can lead to electrolyte disorders, cardiomyocyte dysfunction, induce cardiac arrhythmias, and high temperature can also lead to peripheral vascular dilatation and reduced coronary blood flow [8], And cause arrhythmia and heart failure and other cardiovascular diseases.…”
Section: Temperature and Cardiac Arrestmentioning
confidence: 99%
“…Though her information was subsequently removed, it caused worry for advocates of open access that privacy concerns might significantly slow the progress of Big Data research. Nevertheless, health data collected without personal information would still provide accurate research findings to understand exact occurrence time, temperature, age and gender that affecting our life in out-of-hospital cardiac arrest situation (Low et al, 2018).…”
Section: Privacy Concernsmentioning
confidence: 99%